Private Bond Restructurings : Lessons for the Case of Sovereign Debtors - Pinon-Farah, Marco (Washington, D.C. : International Monetary Fund, 1996)
This paper reviews recent experience with both sovereign and private bond restructurings. It also summarizes the literature on private bond restructurings and describes the 'typical' process for a voluntary exchange of new bonds for existing obligations. From this information some conclusions are drawn as to the possibility of concluding voluntary restructuring agreements for sovereign bonds within relatively short periods of time.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet